Meningkatkan prestasi belajar matematika siswa kelas XII TKJ A SMKN 3 Tabanan melalui penerapan pembelajaran berbasis masalah dengan teknik diskusi kelompok - I Gede Budiarsa (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
This research was conducted at Tabanan State Vocational School 3 in Class XII TKJ A, where the ability of students for Mathematics material was quite low. The purpose of writing this Classroom Action Research is to find out whether